Prognostic impact and the relevance of PTEN copy number alterations in patients with advanced colorectal cancer (CRC) receiving bevacizumab1. (25th March 2013) - Price, Timothy J.; Hardingham, Jennifer E.; Lee, Chee K.; Townsend, Amanda R.; Wrin, Joseph W.; Wilson, Kate; Weickhardt, Andrew; Simes, Robert J.; Murone, Carmel; Tebbutt, Niall C.
Abstract Loss of phosphatase and tensin homologue (PTEN) expression may be prognostic in colorectal cancer (CRC) and may have a correlation with vascular endothelial growth factor (VEGF) expression via hypoxia‐inducible factor 1 (HIF‐1) alpha, and the PI3K/mTOR pathways. We therefore have explored the prognostic association of PTEN loss and the potential that PTEN loss may be predictive of outcome with bevacizumab. Patients enrolled in the AGITG MAX trial, a randomized Phase III trial of capecitabine (C) +/− bevacizumab (B) (+/− mitomycin C [M]) with available tissues were analyzed for PTEN expression (loss vs. no loss) as assessed using a Taqman® copy number assay (CNA). Of the original 471 patients enrolled, tissues from 302 (64.1%) patients were analyzed. PTEN loss was observed in 38.7% of patients. There was no relationship between PTEN loss and KRAS or BRAF mutation. PTEN status was not prognostic for progression‐free survival (PFS) or overall survival (OS) in multivariate analyses adjusting for other baseline factors; loss versus no loss PFS hazard ratio (HR) 0.9 (0.7–1.16), OS HR 1.04 (0.79–1.38). PTEN was not prognostic when assessed by KRAS and BRAF status. By using the comparison of C versus CB+CBM, PTEN status was not significantly predictive of the effectiveness of B for PFS or OS. PTEN status was not prognostic for survival in advanced colorectal cancer, irrespective of KRAS or BRAF status. PTEN status did not significantly predict different benefit with bevacizumb therapy.